Historie afektywne i polityki pamięci (Instytut Badań Literackich Polskiej Akademii Nauk, 2024)
The volume Affective Histories situates affect as a key notion, which combines various perspectives that break the rational forms of experiencing reality. The authors reveal numerous faces of contemporaneity seen through the prism of an affective understanding of history, often traumatic or uncanny (unheimlich). How do moods, emotions or passions imprint on the communal frameworks of memory? Or, perhaps the affective modalities which elude awareness (and yet, they somehow constitute it), extract memory from socially determined norms, releasing new constellations of identity and communities of beings, which are only connected by the awareness of their own otherness? Difficult to chart, the affective trajectories threaded onto one another traverse and transform the text, context and experience of the receiver of a piece of art, literature, or philosophical thought. And yet, affective ephemera leave lasting marks, or, in the words of Avishai Margalit, ‘scars of memory’, which the authors of the present texts trace with a passion. There is a Gestalt of identity which is global, yet domesticated in itself; alienated, and yet rooted in a world of the intimacy of an experiencing body, which is close to it. Affective variety, permeating every corner of being, breaking the anthropocentrically-established model of complete existence, allows for a revealing of affective ‘separated’ communities, which, being far from passive, are actually gifted with ethical-political agency. (Prof. Dorota Głowacka)